The trial of David Lurie: Kafka's courtroom in Coetzee's Disgrace. Issue 3 (15th April 2016) - Conti, Christopher
Abstract : J. M. Coetzee's affinity with Franz Kafka is bound up with the weakly messianic role Kafka plays in modernist aesthetic theory and the philosophical discourse of modernity. The redemptive aesthetic of modernist allegory modelled on Kafka implies a philosophy of history that, by giving metaphysical scope to the ideas of justice and guilt, puts modernity on trial. Reading Coetzee's Disgrace alongside Kafka's Trial complicates the familiar allegory of state persecution, however, and suggests the persistence of myth in modernity as an enabling device that reveals as much of the moral autonomy of the subject as it does its entrapment in the rationalised relations of modern life.